Ensino de História e Direitos Humanos: a construção da aprendizagem histórica através da gamificação - PENNA, Teresa Helena Mendonça Correa Garcia (2022)
This research aims to analyze the connections between History teaching and Human Rights Education and the importance of using gamification as a resource and teaching strategy. Human Rights Education as an interdisciplinary practice in basic education, includes discussions on human rights violations in high school history classes based on didactic approaches related to the Second World War, taking the Holocaust and religious intolerance as a focus. Thus, we analyzed several authors such as Benevides (2000), Hunt (2009), Santos (2014) and Piovesan (2007) on human rights, Daros and Camargo (2018), Bacich (2018) and Moran (2018) on active methodologies, Alves (2015), Filatro and Cavalcanti (2018) on gamification, Bitterncourt (2018), Boto (2005), Rüsen (2015), Schmidt (2014), Fonseca (2010) on the didactics and methodology of teaching History. From a bibliographic investigation to develop both the research and the product, we consider the historical aspects and the educational legislation that guide the principles of education and education in human rights, contained in the National Plan for Education in Human Rights (PNEDH, 2013) and in the National Curricular Common Base (BNCC, 2018). In this way, the approach focused on the pedagogical praxis of the History teacher, based on the understanding of teaching and mediation, based on these universal principles, and on the difficulties related to mastering technologies in the classroom. Finally, we seek, through the elaboration of an e-book, aimed at educators of Basic Education, to present the results obtained with the research, highlighting relevant issues on the subject, in the perspective of creating an opportunity to deepen the debate in the classroom and the use of technologies by applying gamification as a methodological resource, motivating teachers and students to practice an active citizenship and the understanding of being protagonists of history and transforming agents of the social reality in which they are inserted.